Community-based Maternal and Child Nutrition and Health Interventions in Nigeria : A Comparative Case Study Analysis on Best Practices - World Bank (World Bank, Washington, DC, 2013)
This study discusses how to effectively engage in community-based nutrition and health programs aimed to improve maternal, newborn, and child nutrition and health outcomes, particularly in Northern Nigeria. It provides the comparative synthesis of four case studies, each of which included a community action component for improving nutrition and health outcomes. It provides a normative base for designing and planning government programs that support reforms in outcome-based programming for maternal, newborn, and child nutrition and health through program support and investment lending. Central to the report is the discussion on the roles played by various stakeholders - state and local government, NGOs, traditional and religious leaders, and communities themselves - in creating and sustaining community mobilization. The factors considered essential or useful contributors to community mobilization are analyzed. The history of government s role in Nigerian health care is discussed, as well as the current situation and future possibilities, especially at the state and local level.